THE ESSENCE AND SIGNIFICANCE OF ATTENTION TO THE HERITAGE OF OUR GREAT SCHOLARS IN NEW UZBEKISTAN (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the large-scale work being carried out in New Uzbekistan to study and widely promote the rich scientific and spiritual heritage of the great scholars of the region. It reviews the activity of the scholarly institutions established for this purpose, their cooperation with international organisations such as IRCICA, ICESCO, and UNESCO, and the state’s attention to figures such as Imam al-Bukhari. It surveys the contributions of leading scholars – among them Imam al-Bukhari, al-Maturidi, al-Zamakhshari, al-Marghinani, al-Khwarazmi, Ibn Sina, al-Farghani, Mirzo Ulugbek, and Alisher Navoi – and concludes with a set of recommendations for the further study of this heritage, including the cataloguing and investigation of the manuscripts preserved in Uzbekistan.
Keywords: scholarly heritage, New Uzbekistan, Imam al-Bukhari, al-Maturidi, al-Zamakhshari, al-Khwarazmi, Ibn Sina, manuscripts, Third Renaissance, Islamic civilisation.